Research progress on the mechanism of radiation enteritis - Fan, Jinjia; Lin, Binwei; Fan, Mi; Niu, Tintin; Gao, Feng; Tan, Bangxian; Du, Xiaobo (Frontiers in Oncology, 2022)
Radiation enteritis (Re) is one of the most common complications of radiation therapy for abdominal tumors. The efficacy of cancer treatment by radiation is often limited by the side effects of Re. Re can be acute or chronic. Treatment of acute Re is essentially symptomatic. However, chronic Re usually requires surgical procedures. The underlying mechanisms of Re are complex and have not yet been elucidated. The purpose of this review is to provide an overview of the pathogenesis of Re. We reviewed the role of intestinal epithelial cells, intestinal stem cells (ISCs), vascular endothelial cells (ECs), intestinal microflora, and other mediators of Re, noting that a better understanding of the pathogenesis of Re may lead to better treatment modalities.